Student teachers' perceptions of critical thinking and its teaching. (3rd December 2019) - Yuan, Rui; Stapleton, Paul
Abstract: Although the importance of critical thinking (CT) has been stressed in English language education, little attention has been paid to language teachers' perceptions and experiences regarding CT during the pre-service stage of their careers. Drawing on data from a focus group and follow-up email interviews with pre-service language teachers, this study shows that the participants had a limited understanding of CT, and lacked preparation and support in their programmes regarding how to implement CT-oriented teaching practices. The findings also revealed a range of individual and contextual challenges faced by the participants when they tried to integrate CT into their language teaching. The study concludes with recommendations on how to cultivate a critical mindset among language teachers while developing CT-oriented pedagogies.